1999
DOI: 10.1021/jf980347+
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Models of Cytochrome P450 Catalyzed Insecticide Metabolism. Application to the Oxidative Metabolism of Carbamate Insecticides

Abstract: Cytochrome P450 (CP450) catalyzed oxidative metabolism of carbofuran (1), carbaryl (2), and pirimicarb (3) has been modeled using biomimetic oxidations catalyzed by iron(III) tetraarylporphyrins. Oxidation products of 1 were identified by comparison of HPLC retention times measured under standardized conditions for metabolites synthesized and characterized by (1)H and (13)C NMR spectroscopy. Comparison of product distributions to in vivo metabolic profiles revealed that the H(2)O(2)/meso-tetrakis(pentafluoroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Despite the good results obtained with the use of synthetic metalloporphyrins in drug oxidation, few studies have been devoted to the application of these models in pesticide transformation. Keseru ¨and co-workers are one of the few groups working in this field, and they have shown that Fe(TFPP)Cl can mimic the action of insect P450 in the chemical transformation of insecticides belonging to the carbamate class of compounds (7).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the good results obtained with the use of synthetic metalloporphyrins in drug oxidation, few studies have been devoted to the application of these models in pesticide transformation. Keseru ¨and co-workers are one of the few groups working in this field, and they have shown that Fe(TFPP)Cl can mimic the action of insect P450 in the chemical transformation of insecticides belonging to the carbamate class of compounds (7).…”
Section: Introductionmentioning
confidence: 99%
“…metalloporphyrines as synthetic livers, can provide a practical tool for generating such libraries. 19 The MeDiverse set of compounds is a selected, diverse library of 10 000 heterocyclic organic compounds. In that collection all possible metabolites are predicted for each member; therefore, it should be considered as an in vivo metabolically extended library.…”
Section: Resultsmentioning
confidence: 99%
“…To model the major biochemical functions, metalloporphyrins have been recently reported as synthetic livers or mimics of the in vivo metabolic processes. 19 Finally in vitro toxicity screening assays are generally cellular based models, allowing estimation of cell toxicity, mutagenicity, and carcinogenicity. Many companies are turning to in vivo multiple cassettes or "n-in-one" dosing strategies, when multiple compounds are administered to a single animal.…”
Section: Early Adme/tox Assessment For Improved Oral Bioavailabilitymentioning
confidence: 99%
“…3) Among these methods, chemical oxidation by peroxide in the presence of a synthetic iron-porphyrin as a catalyst has been demonstrated to be an effective tool to obtain oxidative degradates for carbamate insecticide, 4) organophosphorus pesticides, 5) insect growth regulator 6) and triazine herbicide. 7) This reaction corresponds to the shunt pathway in CYP450 catalysis to produce the reactive intermediate, oxoiron (IV) porphyrin cation radical, (d) in Fig.…”
Section: Introductionmentioning
confidence: 99%